GERAKAN BKSWI (BADAN KERJASAMA WANITA ISLAM) DALAM PERUBAHAN SOSIAL - Masrifah Masrifah (FISIP UIN SGD Bandung, 2018)
This article focuses on a women’s movement, BKSWI, in a country led primarily by males, Indonesia. This masculine condition could not resist any response moved by Muslim women such as BKSWI and marched towards its program of modernization. The approach to discover BKSWI’s movement is the study of of descriptive in which biographical and sociological are among the methods. The main BKSWI’s response being discussed here is Indonesian social context bringing about the issues of participation of women in social welfare, especially through the managing of Islamic hospitals. It should be noted, however, that all data related are mainly in Indonesia’s context of contemporary.